Pengaruh Model Pembelajaran Kontekstual terhadap Hasil Belajar Siswa di Pondok Pesantren Roudlotul Ulum - Ayubi, Ibnu Imam Al; Murharyana; Azizah, Azzah; Nuroh, Annisa Siti; Yasmin, Sabrina; Maulana, Cep Hasbi (Al-Wasathiyah: Journal of Islamic Studies, 2024)
This research aims to see whether or not there is an influence on contextual learning for the students at the Roudlotul Ulum Islamic boarding school who inherently received their academic education at the school at the Islamic boarding school. This research was carried out at Roudlotul 'Ulum Middle School using a quantitative approach. This research method uses a survey method with correlation analysis to see the relationship between the independent variables, namely student motivation, and the dependent variable, namely student learning outcomes using the Contextual Teaching Learning (CTL) learning model. The population of this research was class VIII students at Roudlotul 'Ulum Middle School with a sample of 30 students. The specifications for data analysis requirements used consist of normality tests and linearity tests with the hypotheses used, namely correlation and regression tests assisted by SPSS version 26. In this research, it was found that student learning motivation and student learning outcomes used the Contextual Teaching Learning (CTL) learning model with distributed data. normal and correlates with strong coefficient strength with a Correlation Coefficient value of 0.843 and the interaction between learning motivation and learning outcomes is 80.9% and the other 19.1% is influenced by external factors. Because the data is normally distributed, it is continued with a regression test which produces data that meets the linearity criteria with the regression equation being Y=31.642+0.587X.